The Effect of Experiential Marketing, Customer Perceived Value and Brand Image on Customer Satisfaction - Septian, M. Rizaldi; Harsoyo, Titik Desi (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The development of the food and beverage business in recent years has attracted great interest among young people. The profits obtained are quite large and can apply creativity in innovating with the latest developments and changes in consumer interests. This research aims to analyze the influence of experiential marketing, customer perception value, and brand image on customer satisfaction. The independent variables used in this research are experiential marketing, customer perception value and brand image, while the dependent variable in this research is purchase satisfaction. This research uses a causal quantitative approach. Data collection was carried out by distributing questionnaires to 100 respondents who had purchased Mixue. The question items for all variables were proven to be valid and reliable. The results of this research are that experiential marketing has a positive and significant influence on customer satisfaction. The value perceived by customers also has a positive and significant influence on customer satisfaction. Brand image does not have a significant influence on customer satisfaction.